A boulder-strewn tidal flat, north shore of the Gulf of St. Lawrence, Québec - Dionne, Jean-Claude (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1981)
A clay flat strewn with ice-drifted boulders occurs in a sheltered embayment near Harrington Harbour, North Shore of the Gulf of St. Lawrence. The embayment, approx. 7 km2 in area with a slope gradient less than 0.2°, is under the influence of tides ranging from 1.4 to 2.2 m and of a low wave energy regime. Ice entirely covers the flat during 3 to 4 months per year but may be present up to 5 months. Ice rafting, ice pushing, and ice gauging are moderately important processes in the embayment.